The sustainability characteristics of Michelin Green Star Restaurants - Huang Y; Hall CM; Chen NC (Taylor and Francis Group, LLC, 2025)
The restaurant industry in increasingly aware of sustainability issues with around 34% of anthropogenic greenhouse gas emissions come from life-cycle stages in food systems and increased concerns over packaging and food waste. The Michelin Restaurant Guide has awarded the distinction of a Green Star to restaurants at the forefront of the industry in their sustainability. However, although restaurant sustainable practices are often presented in food media, the characteristics of sustainability-awarded restaurants are often unknown. This study aims to identify the extent to which sustainability is promoted by Michelin Green Star Restaurants (MGSRs) as part of their online offerings. By conducting a website content analysis of 355 MGSRs, this study examines eight sustainability initiatives during food procurement, preparation, and presentation. The results suggest that MGSRs could be sustainability ambassadors and promoters, but currently, they are modest in promoting sustainability. Most MGSRs’ websites highlight their selection of local and organic food but place less emphasis on sustainable practices in food preparation, even though some of them are practising sustainability in reality. This study suggests that restaurants could be sustainability ambassadors by putting sustainable practices on their websites as well as on the “customer’s plates”.
Keywords: Sustainable restaurants; Michelin guide; fine-dining restaurant; food system; sustainable food service practices